Vanadium contamination and associated health risk of farmland soil near smelters throughout China. (August 2020) - Li, Yi'na; Zhang, Baogang; Liu, Ziqi; Wang, Song; Yao, Jun; Borthwick, Alistair G.L.
Abstract: Whereas there is broad consensus that smelting causes serious soil contamination during vanadium production, little is known about the vanadium content of soil near smelters and the associated health risk at continental scale. This study is the first to map the distribution of vanadium in farmland soil surrounding smelters throughout mainland China, and assess the associated health risk. Analysis of 76 samples indicated that the average vanadium content in such soil was 115.5 mg/kg – far higher than the 82 mg/kg background content in China ( p  < 0.05). Southwest China (198.0 mg/kg) and North China (158.3 mg/kg) possessed highest vanadium contents. Vanadium content was strongly related to longitude, altitude, and atmospheric temperature. The reducible fraction accounted for the largest percentages in vanadium speciation. The average Pollution Load Index for all samples was 1.51, denoting significant metal enrichment. The Children's hazard index was higher than unity, indicating elevated health risk. The relative contribution of vanadium to the total health risk ranged from 6.02% to 34.5%, while nickel and chromium were the two main contributors in most regions. This work may serve as a model providing an overview of continental vanadium contamination around smelters, and draw attention to their possible health risks. Graphical abstract: Image 1 Highlights: 76 farmland soil samples around vanadium smelters taken throughout China. Average vanadium content is 115.5 mg/kg, with elevated levels in SC and NC. Reducible fraction accounts for the largest percentages in vanadium speciation. Significant enrichment of metals and elevated health risk are found. The relative contribution of vanadium to health risk ranges from 6.02% to 34.5%.